The Role Of Islamic Banks In Increasing The Financial Inclusion Of The People Of Panyabungan City, Mandailing Natal District - Jureid, Jureid; Iska, Syukri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Islamic banking in Indonesia has grown significantly, but its services remain unevenly distributed, especially in rural areas like Mandailing Natal Regency, where only 30% of residents access formal financial services (BPS, 2023). This study examines the role of Islamic banks in improving financial inclusion in Panyabungan City. Using a quantitative method and 100 respondents, data were collected via structured questionnaires and analyzed with PLS-SEM. Results show that financial literacy (β = 0.422; p = 0.000) and perception of Islamic banks (β = 0.493; p = 0.000) significantly affect financial inclusion, with R² = 0.647. Despite high account ownership, digital service use and financing remain low. Findings underscore the importance of strengthening financial literacy and expanding access to Islamic digital banking. Recommendations include targeted financial education and outreach strategies to enhance service utilization in underserved regions